**Balance the following equation stepwise.SO2(g) + H2S(aq) → S(s) + H2O (l)**

__Balanced equation:__ SO2(g) + 2H2S(aq) 3S(s) + 2H2O (l)

**Explanation:**

⇒ Step 1: Write the given unbalanced equation

SO2(g) + H2S(aq) S(s) + H2O (l)

⇒ Step 2: Compare the number of atoms of reactants with the number of atoms of products.

⇒ Step 3: Now, let us consider oxygen atom. If we multiply 2 in the product (in H2O), we will get the equal number of atoms as in reactants (SO2)

⇒ Step 4: Write the resulting equation:

SO2 + H2S S + 2H2O

⇒ Step 5: Now check whether the equation is balanced or not by comparing the atoms

We find that the equation is not balanced yet. As the number of

sulphur and hydrogen atoms are unequal on the two sides.

First balance the hydrogen number.

⇒ Step 6: Now, let us consider hydrogen atom. If we multiply 2 in the reactant (in H2S), we will get the equal number of atoms as in product (H2O)

⇒ Step 7: Write the resulting equation:

SO2 + 2H2S S + 2H2O

⇒ Step 8: Now check whether the equation is balanced or not by comparing the atoms

We find that the equation is not balanced yet. As the number of

sulphur atom is unequal on the two sides.

⇒ Step 9: Now, let us consider sulphur atom. If we multiply 3 in the product (S), we will get the equal number of atoms as in reactants (SO2 and H2S)

⇒ Step 10: Write the resulting equation:

SO2 + 2H2S 3S + 2H2O

⇒ Step 11: Now, compare the atoms of both the sides of all the elements. Write down the final balanced equation:

SO2 + 2H2S 3S + 2H2O